The Bahamas. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in Bahamas during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as apiculture, agribusiness, public policy, agritourism, governance, resilience against climate change, and food safety and health, through the use of the Codex Alimentarius. Likewise, work was done to improve livestock management and nutrition, pathogen management and customer service. Finally, agricultural value chains were strengthened.